Politics of Islam in Javanese Aesthetics: R. Ng. Yasadipura I’s Poe(li)tical Imagination of Islam in Babad Tanah Jawi - Achmad Fawaid; Wening Udasmoro; Sri Margana; Bannaga Taha Al-Zubair Hussen (UIN Sunan Gunung Djati Bandung, 2022)
This paper is to figure out R. Ng. Yasadipura I’s poe(li)tical imagination of Islam in Babad Tanah Jawi. The ‘politics’ is defined not merely as instrumental utility, but intertwined with ‘poetics’, an aesthetic strategy which allegorically unveils an interpretation of the undecidability of Islam as central Islam or peripheral Islam, as Arabia Islam or Javanese Islam. Based on the biographical and structural approaches, this article attempts to analyze textual, ideological, and religious traces of this 18th century Javanese Muslim bhujangga and its relation to the way he describes Islam in Babad Tanah Jawi. Yasadipura I is a political subject, since he describes Islam not merely as a religious consensus, but also dissensus to other identities. This dissensus is partly a logical consequence of—using Jacques Rancière’s term—Yasadipura I’s ‘class migration’, ranging from Muslim student (santri) from Kedu, royal advisor (menteri) of Surakarta court, to prolific writer and translator of Hindu-Buddhist kakawin and Islamic Malay suluk.